The ED-PACT Tool Initiative: Communicating Veterans' Care Needs After Emergency Department Visits. Issue 3 (May 2020) - Cordasco, Kristina M.; Saifu, Hemen N.; Song, Hyun-Sung; Hsiao, Jonie J.; Khafaf, Mana; Doyle, Brian; Rubenstein, Lisa V.; Chrystal, Joya G.; Bharath, Purnima; Ganz, David A.
ABSTRACT: Background: Communication failures between providers threaten patient safety. Purpose: We developed, implemented, and formatively evaluated the ED-PACT Tool, which uses the Veterans Health Administration's (VA) electronic health record to send messages from emergency department (ED) providers to primary care patient-aligned care team (PACT) registered nurses (RNs) for Veterans discharged home from the ED with urgent or specific follow-up needs. Methods: We used Plan-Do-Study-Act quality improvement methodology. Results: Between November 1, 2015, and November 30, 2017, the tool was used to send 4, 899 messages in one local VA healthcare system (ED and associated primary care clinics). Formative evaluation revealed that providers and RNs perceive the tool as providing substantial benefit for coordinating post-ED care. Patient-aligned care team leaders reported that RN training and "buy-in" facilitated tool implementation, while insufficient staffing posed a barrier. Emergency department providers noted the advantage of having a standardized and reliable system for communicating with PACTs. Conclusions/Implications: The ED-PACT Tool encapsulates several best practices (standardized processes, "closed-loop" communication, embedding into workflow) to facilitate communication between VA ED and follow-up care providers. Our development process illustrates key lessons in quality improvement and innovation implementation including the value of using rapid-cycle improvement methodology, with interprofessional collaboration and representatives from intended spread sites. Abstract : Supplemental Digital Content is Available in the Text.